Pengembangan Model Pembelajaran Problem Based Learning Berbasis Budaya Lokal Masyarakat Pesisir Bengkulu untuk Meningkatkan Sikap Sosial Siswa Sekolah Dasar - Febri Ariffiando , Nady; Susanti, Atika; Yolanda Azaria, Fidela; Darmansyah, Ady (UNIB Press, 2023)
This study aims to produce a problem-based learning model based on the local culture of the Bengkulu coastal community which is assessed for its feasibility, practicality, and effectiveness for improving the social attitudes of elementary school students. The type of research used is research and development with the ADDIE model. Products are validated by material, language and presentation experts. In addition to the validation test, a limited trial was also carried out to test the practicality and effectiveness of product development with teachers and fifth grade students at elementary school 1 Bengkulu City. Testing its effectiveness to improve social attitudes is carried out with a Classroom Action Research design. The data collection instrument used was a validation questionnaire, practicality and effectiveness. The Problem Based Learning model based on the local culture of the Bengkulu coastal community is declared: suitable for use by material, language, and presentation experts with the category